2004
DOI: 10.1111/j.1365-2486.2004.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon flow in an upland grassland: effect of liming on the flux of recently photosynthesized carbon to rhizosphere soil

Abstract: The effect of liming on the flow of recently photosynthesized carbon to rhizosphere soil was studied using 13 CO 2 pulse labelling, in an upland grassland ecosystem in Scotland. The use of 13 C enabled detection, in the field, of the effect of a 4-year liming period of selected soil plots on C allocation from plant biomass to soil, in comparison with unlimed plots. Photosynthetic rates and carbon turnover were higher in plants grown in limed soils than in those from unlimed plots. Higher d 13 C% values were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 55 publications
5
39
0
1
Order By: Relevance
“…The 13 C isotope signal is then tracked in shoots, roots, and rhizosphere soil during the months following the pulse. In grassland sites, very rapid turnover of C has been observed (Rangel-Castro et al 2004). …”
Section: Measuring Changes In Carbon In the Soilmentioning
confidence: 99%
“…The 13 C isotope signal is then tracked in shoots, roots, and rhizosphere soil during the months following the pulse. In grassland sites, very rapid turnover of C has been observed (Rangel-Castro et al 2004). …”
Section: Measuring Changes In Carbon In the Soilmentioning
confidence: 99%
“…Sequences amplified from 13 C-labeled DNA or RNA are derived from organisms actively assimilating the substrate. This approach has been used to identify organisms that utilize methane or methanol (4,19), organic compounds (15,20), or CO 2 (6, 9) in microcosms and those that assimilate plant root exudates in the field (28). SIP therefore links phylogeny to ecosystem function and has identified established and novel groups by utilizing labeled compounds in complex soil communities.…”
mentioning
confidence: 99%
“…Secondly, the 13 C contribution was diluted by the newly unlabeled photosynthetically-fixed C as reed growth proceeded (Rangel-Castro et al 2004). Thirdly, the stronger nutrient competitive abilities for reed demand resulted in smaller size of the rhizosphere microbial biomass (Blagodatskaya et al 2010;Kuzyakov and Blagodatskaya 2015) during reed growth, as shown by the reed N uptake under the N-limited condition in our study (Fig.…”
mentioning
confidence: 57%